DIGONESTIC ENVIRONMENTAL MONITERING SYSTEM IN A POULTRY HOUSE - & et al, Al-Chalabi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This experiment was conducted at a closed poultry house , Poultry Research Station , office of Agricultural Research, Ministry of Agriculture, Baghdad, Iraq, for the period from 2/9 to 14/03/2016 for total rearing of 35 days. To diagnose and monitoring the Environmental factors such as temperature, humidity , density, and the carbon dioxide levels inside the house during winter season, and its impact on the productive performance of broiler chickens Rose 308 breed .The dimensions of the house was ,length 35 m x width 7.5 m x Height 2.5 m, by total space volume 3656.25 m3. The ventilation system in the house was (negative pressure type). The house is totally closed, small fans for (minimum ventilation) in the winter are functioned, and large fans for ventilation in the evaporative cooling operation were used in the summer. 1000 sexed birds were used in this experiment imported through commercial hatchery in Abu Ghraib. The house was divided into three thermal Zones in order to find out whether heterogeneity in environmental conditions is existed in the house and at bird level .as a result the impact on the homogeneity in the weights of marketed birds . The treatments have been distributed into 32 rearing cages by the following order: 8 cages with the density of 50 birds / cage, the remaining 24 cages were divided into the density of 25 birds / cage. The results showed that there were significant differences between the treatments in the rate of body weight ,body weight gain, feed intake and feed conversion efficiency among densities and the three thermal zones due to the presence of cool air leaks into the house at the front ,End of the house, and its sides especially when fans are on , along with dead Air pockets that were identified in many places in the middle of the housed, yet this Zone was the one that had the best productive traits in comparison with the other two zones. The purpose of this experiment is to study environmental parameters homogeneity inside the shed in addition to impact of CO2 levels and impact of birds density on productive traits.